CHALLENGES OF SUSTAINABLE TOURISM IN ANCIENT CITIES: A CASE STUDY BASED ON KANDY, SRI LANKA - Sivesan, S. (University of Jaffna, 2019)
Within the extensive body of tourism literature, successful implication of sustainable tourism and obstacles to its practices in the developing world are emerging themes. This paper critically investigates challenges to sustainable tourism in the world heritage sites with special references to Kandy situated in Central Province of Sri Lanka. Through adopting a qualitative research method, a key issue for discussion in this paper is challenge to sustainable tourism in Kandy. Consequently, this paper provides an insight into sustainable tourism and suggests the ways by which these insights may be useful in the provision of sustainable tourism in other ancient heritage localities.
Keywords: sustainable tourism; destruction of cultural heritage building; tourism infrastructure